2013
DOI: 10.1186/1743-422x-10-276
|View full text |Cite
|
Sign up to set email alerts
|

Rapid emergence of a virulent PB2 E627K variant during adaptation of highly pathogenic avian influenza H7N7 virus to mice

Abstract: BackgroundHighly pathogenic avian influenza (HPAI) viruses pose a potential human health threat as they can be transmitted directly from infected poultry to humans. During a large outbreak of HPAI H7N7 virus among poultry in The Netherlands in 2003, bird to human transmission was confirmed in 89 cases, of which one had a fatal outcome.MethodsTo identify genetic determinants of virulence in a mammalian host, we passaged an avian H7N7/03 outbreak isolate in mouse lungs and evaluated the phenotype of the mouse-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Selected H7 viruses, like the H7N9 LPAI virus, with such mammalian adaption markers have emerged and exhibited increased virulence in animal models (14). Moreover, the PB2 627K mutation present in the H7N7 HPAI NL/219 virus was also found to be responsible for its lethal phenotypes in mammals (32). Sequence analysis of two recently emerged H7N8 viruses reveals no such substitutions, indicating that H7N8 viruses have not become well adapted to infect mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Selected H7 viruses, like the H7N9 LPAI virus, with such mammalian adaption markers have emerged and exhibited increased virulence in animal models (14). Moreover, the PB2 627K mutation present in the H7N7 HPAI NL/219 virus was also found to be responsible for its lethal phenotypes in mammals (32). Sequence analysis of two recently emerged H7N8 viruses reveals no such substitutions, indicating that H7N8 viruses have not become well adapted to infect mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Such evolution has been observed in a fatal human case of influenza A/H7N7 (Jonges et al, 2014) and in mouse experiments following serial lung passage using an isolate from this outbreak (de Jong et al, 2013). Lys at position 627 has also been associated with greater severity in zoonotic H7N9 (Sha et al, 2016) and H5N1 (de Jong et al, 2006) cases However, reverse genetics experiments show that certain strains of avian influenza may be less able to accept these mutations than others (Long et al, 2013).…”
Section: Trait 3: Polymerase Complex Efficiencymentioning
confidence: 80%
“…Similarly, the presence of a lysine at this position in LPAI H7N9 human isolates and a mouse-adapted H7N7 equine virus resulted in increased PB2 polymerase activity, viral loads, and disease severity in mice (Mok et al 2014; Shinya et al 2007; Zhang et al 2013, 2014). Enhanced virulence of HPAI H7N7 viruses bearing E627K was also observed in ferrets compared with virus bearing glutamic acid at this position (de Jong et al 2013). However, H7N9 viruses bearing either a glutamic acid or lysine at position 627 exhibited comparable transmissibility in the ferret model, indicating E627K does not solely confer an enhanced transmissibility phenotype (Zhang et al 2013).…”
Section: Molecular and Host Determinants Of Pathogenicity And Transmentioning
confidence: 99%
“…As mentioned in preceding sections, several studies have demonstrated a similar role for this position among H7 subtype viruses. An E627K substitution in a HPAI H7N7 virus isolated from the Netherlands was identified as a major determinant of mammalian pathogenicity, with viruses bearing this mutation exhibiting increased viral load, extrapulmonary spread to the brain, and heightened mortality in mice; this enhanced virulence was absent in mice inoculated with virus bearing the reciprocal K627E mutation (de Jong et al 2013; Munster et al 2007). Similarly, the presence of a lysine at this position in LPAI H7N9 human isolates and a mouse-adapted H7N7 equine virus resulted in increased PB2 polymerase activity, viral loads, and disease severity in mice (Mok et al 2014; Shinya et al 2007; Zhang et al 2013, 2014).…”
Section: Molecular and Host Determinants Of Pathogenicity And Transmentioning
confidence: 99%